The Relationship of Coronavirus Phobia and Technology Addiction in the Faculty of Health Sciences Students in Turkiye During the Coronavirus Disease 2019 Period - Caliskan, Enes; Ersogutcu, Filiz; Kargin, Maral (Turkish Green Crescent Soc, 2023)
This study examined the relationship between coronavirus phobia and technology addiction experienced by health sciences students during the coronavirus disease 2019 pandemic. The current study, structured as a relational and descriptive research design, was conducted with a large public university's Health Sciences Faculty students in Turkiye between March 12, 2021, and April 12, 2021. A total of 1126 volunteer students participated in the study. Personal Information Form, Coronavirus Phobia Scale, and Technology Addiction Scale were used to collect data. Pearson correlation analysis was used to analyze the relationships between the data, and the independent sample t-test and one-way analysis of variance test (Tukey) were used to compare the variables. A significant two-way positive correlation was found between the Technology Addiction Scale and the Coronavirus 19 Phobia Scale (r = 328, p <.01). This study determined that Health Sciences Faculty students with high coronavirus phobia had high technology addiction, and those with low coronavirus phobia had low technology addiction. Under difficult living conditions such as the pandemic, parameters such as phobia and addiction experienced by young people should be taken seriously, and studies should be carried out in this area, because young people, who are the building blocks of our future, will be physically, socially, and psychologically healthy individuals if they can effectively cope with the difficult situations and the differences they create.
Keywords: COVID-19; Health Sciences Faculty students; pandemic; phobia; technology addiction